Dissecting autonomy in a resource-constrained setting: adescriptive qualitative study of women’s decisions on thesurgical treatment of early breast cancer in northern Sri Lanka - Ramya, K.; Gopikha, S.; Dhivya, T.; Chrishanthi, R. (Taylor & Francis, 2025)
Breast cancer treatment is a contested space in which therapeutic decisions often collide withwomen’s values and preferences. In northern Sri Lanka, mastectomy remains the mainstay of surgicaltreatment of early breast cancer (EBC) despite evidence of equivalent survival following breast conservingsurgery (BCS) and radiotherapy. This study explores autonomy in decision-making among women with EBCwho were eligible for BCS and underwent mastectomy in northern Sri Lanka. A descriptive qualitative studywas carried out among 15 women referred for adjuvant therapy to Tellippalai Trail Cancer Hospital in Jaffnadistrict after having a mastectomy for EBC. Participants were recruited between January and May 2022 untildata saturation was reached. Data were gathered through semi-structured interviews, which weretranscribed in Tamil, translated into English, coded using QDA Miner Lite software, and analysedthematically. Women’s autonomy in EBC treatment decisions is limited by various factors in northern SriLanka. The hospital setting is not conducive to informed decision-making, and women do not receivesufﬁcient information. Neither survival rates nor risks/beneﬁts of the surgical options are discussed in asystematic way. Although many women appear to be satisﬁed with their involvement in decision-making,their decisions are guided by incomplete information and fears of spread/recurrence communicated bytreating teams. In the absence of policies and protocols to support patient autonomy, women “choose” themore invasive option: mastectomy. While it behoves medical professionals to provide evidence-basedinformation, governments and the global health community must support strengthening healthcare systemsto advance women’s health and rights in lower-resource settings.
Keywords: Patient autonomy; Breast cancer; Mastectomy; Breast conservation therapy; SriLanka